Genetic modification of chicken germ cells - Park, Tae Sub (Blackwell Publishing Inc, 2012)
Over the past two decades numerous reports have demonstrated that the genetic modification of poultry genomes has great potential for improving poultry production; moreover, it may be used as a powerful tool for the production of industrial proteins. To date, transgenic techniques have been established for generating transgenic birds that express recombinant human proteins in hen eggs, as well as tissue-specific genes as an animal model. The production of transgenic birds is a promising approach that could have practical applications in agriculture and biopharmacology, in addition to advancing our understanding of avian biology. Finally, germ cell–mediated transgenesis could provide a more efficient strategy for creating gene-targeted insertions and deletions in avian species.